(untitled) (Medico Legal Update, 2020)
The causes of hepatic damage to DHF are mixed. Dengue virus can infect the liver and cause damage. Histopathology of the liver in cases of fatal dengue shows that hepatocytes and Kupffer cells can be the target of viral replication and there is involvement of apoptotic mechanism. This study aims to determine the association between dengue virus NS1 protein and degree of clinical manifestation of dengue infection with hepatic dysfunction. Blood samples after taking the serum, were examined for dengue virus NS1 protein and SGOT and SGPT examinations at the Surabaya Health Laboratory Center. Data analysis used Chi Square, Fisher’s Exact, Anava and Dunnet (a = 0.05). The results shows that the correlated variable significantly with dengue hemorrhagic manifestation degree was dengue virus NS protein1 (p = 0.047), with correlation strength of 26.8%. Variables significantly correlated with liver dysfunction were degree of clinical manifestation of dengue fever (p = 0.037) with correlation strength of 33.5% and dengue virus NS protein1 (p = 0.023) with correlation strength of 29.3%. There was a significant relationship between the presence of dengue virus NS1 protein and the incidence of DHF. There was a significant relationship between the presence of dengue virus NS1 protein with hepatic dysfunction (SGOT and SGPT) in dengue virus infection.